RECOMBINATION OF HEAVY AND LIGHT CHAINS OF HUMAN γA-MYELOMA PROTEINS: FORMATION OF HYBRID MOLECULES AND CONFIGURATIONAL SPECIFICITY - Prendergast, Robert A. (The Rockefeller University Press, 1966)
The present studies demonstrate that the conditions necessary for reductive cleavage, isolation, and recombination of L and H polypeptide chains of human γA-myeloma globulins parallel those required for similar manipulation of the component chains of γG-globulin. Specificity of recombination was shown for chains derived from the same protein. In contrast, no intradass preferential recombination was demonstrable. Hybrid molecules, formed by reassociation of noncovalent bonds, could be synthesized from isolated chains of two immunoglobulin classes resulting in the formation of molecules of the type γA-H-γG-L and γG-H-γA-L. Several sera containing both γA- and γG-"monoclonal" peaks were studied, one of which demonstrated the L chains associated with both peaks to be identical both by electrophoretic mobility in acid-urea gel and antigenic analysis. The possibility is considered that this case represents a naturally occurring analogue of the artificially produced hybrid molecules described in this study. Configurational antigenic specificity of γA-myeloma proteins, imposed by the presence of kappa L chains in native and appropriately recombined molecules, provides a further indication of the importance of noncovalent bonds in the establishment of the quaternary structure of these proteins.